The society’s perceptions on the use of fintech services in sharia financial institutions - Rinrin Yuspita; Silviana Pebruary; Aulia Zahra Husnil Kamala (Faculty of Economics, Universitas Islam Indonesia, 2019)
In the development of industrial revolution 4.0, sharia financial institutions keep improving their product innovation through the use of financial technology (fintech). Through development and innovation, society is expected to keep up to date with the current financial services. This research aims to investigate how the interest in using sharia services affected by several factors, such as convenience, benefits, attitude, and suitability. This research uses a descriptive quantitative method through multi-linear regression analysis. The population of the research is Jepara people who use sharia fintech services. The sample is selected through incidental sampling. The research findings reveal that convenience, attitude, and benefit affect sharia fintech users' perceptions of the use of services provided by sharia financial institutions. Meanwhile, trust and suitability do not affect users' perceptions.